Smart Irrigation Solutions: An IoT-Based Mobile Application for Optimized Watering in Modern Agriculture - Ng, Wei Kang; Mat Nawi, Rosmamalmi (Applied Information Technology And Computer Science, 2025)
The Smart Irrigation Solutions is an IoT-based application designed to automate irrigation, reducing the need for manual intervention. This application aims to minimize issues like over or under-irrigation while simplifying the irrigation process through a mobile application. The application contains seven main modules. The User Management module handles account registration, login, and profile management. The Device Management module enables users to add, remove, and manage IoT devices. Environmental Monitoring & Irrigation Control module displays real-time data and automates irrigation. Weather Integration module fetches weather forecasts for irrigation decisions. Plant Management module provides plant details. Notifications module alert users to key events, while Reporting & Logs module generate historical data reports for analysis. It integrates with sensor and weather forecasts to optimize irrigation and ensure crops receive the right amount of water. This project contributes to modern agricultural by promoting water conservation, increasing crop yield, and reducing labor required.